THE SECOND WORLD WAR IN AMERICAN LITERATURE. - Gulomjonova Shahzoda; Eldorbek Hamitov Erkinovich (TADQIQOTLAR.UZ, 2024)
Global culture underwent a significant transition as a result of World War II, and these consequences are still evident today. It is important to note that the majority of the physical carnage was separated from one of the war's main donors, the United States, by an entire ocean. Soldiers had to be sent overseas, and the only things available to the civilians who stayed behind to engage with the war were propaganda and their own imaginations. Because of this, the United States' post-war experience was very different from that of other European nations, and its post-war cultural psychology was especially distinct.